Hydrogen Peroxide Induces Muscle Nociception via Transient Receptor Potential Ankyrin 1 Receptors. (October 2017) - Sugiyama, Daisuke; Kang, Sinyoung; Arpey, Nicholas; Arunakul, Preeyaphan; Usachev, Yuriy M.; Brennan, Timothy J.
Abstract : Background: H2 O2 has a variety of actions in skin wounds but has been rarely studied in deep muscle tissue. Based on response to the transient receptor potential ankyrin 1 antagonists after plantar incision, we hypothesized that H2 O2 exerts nociceptive effects via the transient receptor potential ankyrin 1 in muscle. Methods: Nociceptive behaviors in rats (n = 269) and mice (n = 16) were evaluated after various concentrations and volumes of H2 O2 were injected into the gastrocnemius muscle or subcutaneous tissue. The effects of H2 O2 on in vivo spinal dorsal horn neuronal activity and lumbar dorsal root ganglia neurons in vitro were evaluated from 26 rats and 6 mice. Results: Intramuscular (mean ± SD: 1, 436 ± 513 s) but not subcutaneous (40 ± 58 s) injection of H2 O2 (100 mM, 0.6 ml) increased nociceptive time. Conditioned place aversion was evident after intramuscular (–143 ± 81 s) but not subcutaneous (–2 ± 111 s) injection of H2 O2 . These H2 O2 -induced behaviors were blocked by transient receptor potential ankyrin 1 antagonists. Intramuscular injection of H2 O2 caused sustained in vivo activity of dorsal horn neurons, and H2 O2 activated a subset of dorsal root ganglia neurons in vitro . Capsaicin nerve block decreased guarding after plantar incision and reduced nociceptive time after intramuscular H2 O2 . Nociceptive time after intramuscular H2 O2 in transient receptor potential ankyrin 1 knockout mice was shorter (173 ± 156 s) compared with wild-type mice (931 ± 629 s). Conclusions: The greater response of muscle tissue to H2 O2 may help explain why incision that includes deep muscle but not skin incision alone produces spontaneous activity in nociceptive pathways. Abstract : The injection of H2 O2 solutions into muscle but not more superficial skin tissues caused nociceptive behaviors in rats that were blocked by transient receptor potential ankyrin 1 antagonists. Experiments using capsaicin nerve block suggested that unmyelinated nociceptive neurons transmit nociceptive signals after H2 O2 administration.